High-speed sinter-forging of annular ring component - Singh S.; Jha A.K.; Kumar S. (My University, 2025)
The forging of sintered metal powder preforms is currently arousing interest in many parts of the world as an economic method of producing components from metal powders. The present investigation has been undertaken with a view to analyze the high-speed axi-symmetric sinter-forging of annular ring component by upper bound method taking barreling into consideration. The exponential velocity field and strain rates have been derived using compatibility equation formulated from suitable yield criterion for sintered porous preforms. The average die load has been estimated based on energy dissipated in form of internal deformation, interfacial friction losses and inertia forces. The effect of die velocity on inertia energy has been critically studied using inertia factor. The relationship between interfacial frictional stress and other process variables are illustrated. The interaction of various parameters during high-speed sinter-forging of ring component are discussed and presented graphically also. It is believed that the study will be useful for the assessment high-speed forging of sintered materials.